SCHOOL BULLYING, DITINJAU DARI SUDUT PANDANG HUKUM (DAMPAK DAN PENANGANAN) - Tom Alfa S. Reumi; Winna Amelia A. Senandi (LPPM Uncen, 2019)
The implementation of science and technology (IPTEKS) in the form of counseling with the title